STUDENTS’ COMPETENCY IN USING LEARNING RESOURCES ON THE LEARNING MANAGEMENT SYSTEM AT HANOI NATIONAL UNIVERSITY OF EDUCATION - Quoc Khanh, Mai; Trung Kien, Phan (HNUE Journal of Science: Journal of Educational Science, 2025)
This study evaluates the competency of using learning materials within the LMS at Hanoi National University of Education (HNUE LMS), involving 827 students from the faculties of Literature, History, Social Work, and Psychology and Education, within the Social Sciences sector. Research methods include surveys via questionnaires, document analysis, and statistical data processing using SPSS 20 software, employing a rating scale from 1 (poor) to 5 (excellent). Findings indicate that students' competency in utilizing learning materials is moderately good (M = 3.28); however, their skills in linking learning materials to academic tasks remain limited (M = 3.13). Factors influencing this competency include the quality of learning materials, technical infrastructure, students' learning attitudes, and their information technology skills. Based on these results, the study suggests solutions including organizing LMS training programs, upgrading technical support, enhancing the quality of learning materials, and developing a flexible learning environment to improve students' competencies in using learning resources, thereby enhancing overall academic effectiveness.